The Association of Postoperative Complications and Hospital Costs Following Distal Pancreatectomy - Weinberg, Laurence; Ratnasekara, Vidhura; Tran, Anthony T.; Kaldas, Peter; Neal-Williams, Tom; D’Silva, Michael R.; Hua, Jackson; Yip, Sean; Lloyd-Donald, Patryck; Fletcher, Luke; Ma, Ronald; Perini, Marcos V.; et al. (Frontiers in Surgery, 2022)
Background. Understanding the financial implications associated with the complications post-distal pancreatectomy (DP) may be beneficial for the future optimisation of postoperative care pathways and improved cost-efficiency. The primary outcome of this retrospective study was the characterisation of the additional cost associated with postoperative complications following DP. The secondary outcome was the estimation of the prevalence, type and severity of complications post-DP and the determination of which complications were associated with higher costs. Methods. Postoperative complications were retrospectively examined for 62 adult patients undergoing distal pancreatectomy at an Australian university hospital between January 2012 and July 2021. Complications were defined and graded using the Clavien–Dindo (CVD) classification system. In-hospital cost of index admission was calculated using an activity-based costing methodology and was reported in US dollars at 2021 rates. Regression modelling was used to investigate the relationships among selected perioperative variables, complications and costs. Results. 45 patients (72.6%) experienced one or more postoperative complications. The median (IQR) hospital cost in US dollars was 31.6% greater in patients who experienced complications compared to those who experienced no complications ($40,717.8 [27,358.0–59,834.3] vs. $30,946.9 [23,910.8–46,828.1]). Costs for patients with four or more complications were 43.5% higher than for those with three or fewer complications (p = 0.015). Compared to patients with no complications, the median hospital costs increased by 17.1% in patients with minor complications (CVD grade I/II) and by 252% in patients who developed major complication (i.e., CVD grade III/IV) complications. Conclusion. Postoperative complications are a key target for cost-containment strategies. Our findings demonstrate a high prevalence of postoperative complications following distal pancreatectomy with number and severity of postoperative complications being associated with increased hospital costs. (Registered in the Australian New Zealand Clinical Trials Registry [No. ACTRN12622000202763]).